Dampak Pengumuman Hasil Pemilu Presiden Republik Indonesia Tahun 2019 Terhadap Saham Indeks Idx30 - sarah usman; Devid Anggra Kurnia; Dirarini Sudarwadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research examines the impact of the President and vice-Presidential 2019-2024 period election results against shares in the IDX30 index. The research aims to see the difference in the average trading volume activity shares between before and after the announcement. This research uses quantitative approaches with a comparative problem. The sample are all company shares included in the IDX30, actively traded and do not take corporate action at the time before and after the announcement of the President and Vice President. This research will compare the average trading volume acivity between before and after the announcement of the recapitulation results. Statistical testing is the Kolmogorov-Smirnov test, followed by a different test, the Paired Sample T-Test analysis test, the Wilcoxon Signed Rank analysis test. The result of the Wilcoxon signed rank test is 0.01 <0.05, which means the different trading volume activity is significant, the average is decrease. Investors are expected to consider buying shares after the announcement. This means that political events, namely the announcement of the recapitulation of the election of President and Vice President for the 2019-2024 period, affect the trading volume activity in the IDX30 index. For this reason, investors may consider buying shares after the announcement. Keywords: Political Event, Trading Volume Activity